Dampak Dimensi Intellectual Capital Terhadap Knowledge Management Pendamping Desa di Kabupaten Kerinci - Ayu Esteka Sari; Salamah Salamah; Albetris Albetris (Universitas Batanghari, 2019)
In the context of realizing national development goals, the government is paying maximum attention to rural development. The great attention to the countryside is based on the fact that the village is home to a large part of the Indonesian people. The position of the village and the village community is the basis of the life of the nation and state of Indonesia. Intellectual capital is the main strength in an organization, which includes information, technical practitioners, expertise, intellectual property. Village assistance is carried out by village assistants whose job is to assist villages in the implementation of village development and village community empowerment. The objectives of village assistance include: 1) increasing the capacity, effectiveness and accountability of village governance and village development; 2) increase the initiative, awareness and participation of the village community in participatory village development; 3) increase the synergy of inter-sectoral Village development programs; and 4) optimizing village local assets in an emancipatory manner